A plasma protease which is expressed during supramaximal stimulation causes in vitro subcellular redistribution of lysosomal enzymes in rat exocrine pancreas. - Saluja, M (1991)
The complex events by which digestive enzyme zymogens and lysosomal hydrolases are segregated from each other and differentially transported to their respective membrane-bound intracellular organelles in the pancreas have been noted to be disturbed during the early stages of several models of experimental pancreatitis. As a result, lysosomal hydrolases such as cathepsin B are redistributed to the subcellular zymogen granule-rich fraction and lysosomal hydrolases as well as digestive enzyme zymogens are colocalized within large cytoplasmic vacuoles. The current study was designed to create an in vitro system that would reproduce this redistribution phenomenon. Our results indicate that cathepsin B redistribution occurs when rat pancreatic fragments are incubated with a supramaximally stimulating concentration of the cholecystokinin analogue caerulein along with plasma from an animal subjected to in vivo supramaximal caerulein stimulation. Neither the plasma nor a supramaximally stimulating concentration of caerulein, alone, is sufficient to induce in vitro cathepsin B redistribution. The ability of the plasma to induce in vitro cathepsin redistribution is dependent upon its content of a 10,000-30,000-D protein and is lost by exposure to protease inhibitors. In vitro cathepsin B redistribution also occurs when rat pancreatic fragments are incubated with plasma obtained from opossums with hemorrhagic necrotizing pancreatitis caused by bile/pancreatic duct ligation.